До 100-річчя Євгенії Володимирівни Махно - Абашина, Н.С.; Станиціна, Г.О. (Археологія, 2014)
Висвітлено життєвий і науковий шлях відомого археолога, дослідниці черняхівської культури Євгенії Володимирівни Махно. 6 февраля 2013 г. исполнилось 100 лет со дня рождения Евгении Владимировны Махно — одного из ведущих спе циалистов в области раннеславянской археологии. Она начала работать в институте археологии НАН Украины в 1938 г., за год до окончания Киевского государственного университета им. Т. Шевченко. По дороге домой из института 9 сентября 1992 г. оборвалась жизнь исследовательницы. Значительную часть научной деятельности Е.В. Махно составляли полевые исследования — разведки и рас копки. В целом она приняла участие в работе 48 экспедиций, в 30 из них была начальником экспедиции или от ряда. Научное наследие Е.В. Махно — это более 60 публикаций и многочисленные научные отчеты, посвященные памятникам от эпохи бронзы до древнерусского времени, а также своды памятников зарубинецкой и черняхов ской культур. Но главной темой Е.В. Махно было изучение черняховской культуры, которую она считала славян ской. исследовательница также является автором археологической части 25томного издания «история городов и сел Украинской ССр». It was 100 years of birth of yevhenia volodymyrivna Makhno, one of the prominent specialists in the early slavs archaeol ogy, on 6 February, 2013. she started working in the institute of archaeology nas of Ukraine in 1938, the year before she graduated the t. shevchenko kyiv state University. On her way home from the institute the scholar departed this life on 9 september, 1992. Field research, archaeological prospecting and excavation, constituted a significant part of ye.v. Makhno’s scientific activity. On a whole, she took part in the work of 48 expeditions, in 30 of which she was a head of expedition or a group. ye.v. Makhno’s scientific heritage is more than 60 publications and numerous scientific reports devoted to the sites from the Bronze age to the ancient rus period, as well as codes of Zarubynetska and Chernyakhivska cultures monuments. how ever, the main topic for ye.v. Makhno was the study of Chernyakhivska culture which she considered to be slavonic. the scholar also was an author of archaeological part of The History of Cities and Villages of Ukrainian SSR in 25 volumes.